Less cash on the counter: forecasting Finnish payment preferences - Hanna Jyrkönen (Bank of Finland, 2004)
Finnish payment methods have changed rapidly as payment cards have gained increasing popularity and have, to an extent, replaced cash.This article examines this phenomenon and the trends in cash and electronic payment methods in Finland.It starts with an introduction to the statistical data on different payment methods used at points of sale and their electronification, after which learning curve and dynamic regression models are employed to analyse changes in the share of cash payments.Finally, forecasts are presented for the future path of the cash-share.The data indicate that the use of cards, especially debit cards, has increased substantially.For example, in 1984 some 80% of total purchases (in value terms) were made with cash, whereas by 2002 the corresponding figure had dropped below 50%.Estimation results suggest that learning curve models are not suitable for explaining electronification of payment methods in Finland - at least at this stage - whereas the error correction model and its special-case partial adjustment model, coupled with independent explanatory variables, seem to do a better job.A forecast based on the latter indicates that electronification will continue in future and that by 2010 the cash-share of total value of point-of-sale payments will fall to less than 30%.
URN:NBN:fi:bof-20140807424
Keywords: G20; G21; G28; 330; retail payments; payment instruments; electronification